The Impact of Environmental Mn Exposure on Insect Biology - Ben-Shahar, Yehuda (Frontiers in Genetics, 2018)
Manganese (Mn) is an essential trace element that acts as a metal co-factor in diverse biochemical and cellular functions. However, chronic environmental exposure to high levels of Mn is a well-established risk factor for the etiology of severe, atypical parkinsonian syndrome (manganism) via its accumulation in the basal ganglia, pallidum, and striatum brain regions, which is often associated with abnormal dopamine, GABA, and glutamate neural signaling. Recent studies have indicated that chronic Mn exposure at levels that are below the risk for manganism can still cause behavioral, cognitive, and motor dysfunctions via poorly understood mechanisms at the molecular and cellular levels. Furthermore, in spite of significant advances in understanding Mn-induced behavioral and neuronal pathologies, available data are primarily for human and rodents. In contrast, the possible impact of environmental Mn exposure on brain functions and behavior of other animal species, especially insects and other invertebrates, remains mostly unknown both in the laboratory and natural habitats. Yet, the effects of environmental exposure to metals such as Mn on insect development, physiology, and behavior could also have major indirect impacts on human health via the long-term disruptions of food webs, as well as direct impact on the economy because of the important role insects play in crop pollination. Indeed, laboratory and field studies indicate that chronic exposures to metals such as Mn, even at levels that are below what is currently considered toxic, affect the dopaminergic signaling pathway in the insect brain, and have a major impact on the behavior of insects, including foraging activity of important pollinators such as the honey bee. Together, these studies highlight the need for a better understanding of the neuronal, molecular, and genetic processes that underlie the toxicity of Mn and other metal pollutants in diverse animal species, including insects.